Fusion Model in Network Management - Kai Qu; Hong Li; Zhiting Peng; Wenjun Shen (Dianxin kexue)
Integrated network management system is becoming more and more necessary for telecom carriers. Base on the features of network management systems, and according to the practice in area of integrated resource management, a way to build fusion model in integrated network management system for intensive network management was explained, which would solve the problem of stability and extensibility of the core data model.